2021
DOI: 10.48550/arxiv.2104.07823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital quantum simulation of open quantum systems using quantum imaginary time evolution

Hirsh Kamakari,
Shi-Ning Sun,
Mario Motta
et al.

Abstract: Quantum simulation on emerging quantum hardware is a topic of intense interest. While many studies focus on computing ground state properties or simulating unitary dynamics of closed systems, open quantum systems are an interesting target of study owing to their ubiquity and rich physical behavior. However, their non-unitary dynamics are also not natural to simulate on nearterm quantum hardware. Here, we report algorithms for the digital quantum simulation of the dynamics of open quantum systems governed by a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Although many quantum algorithms are known for the simulation of closed quantum systems, fewer studies have considered the simulation of open quantum systems despite their rich and interesting behavior [5]. Current approaches include using inherent qubit decoherence [6,7,8], direct simulation of an environment [9,10,11], implementing Kraus maps / Lindblad operators [12,13,14,15,16], variational techniques [17,18], and more [19,20]. Since Barreiro et al first demonstrated their open-system quantum simulator [21], current early-stage dissipative simulations of quantum systems in the areas of quantum chemistry and physics [19,12,7,22] have been completed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many quantum algorithms are known for the simulation of closed quantum systems, fewer studies have considered the simulation of open quantum systems despite their rich and interesting behavior [5]. Current approaches include using inherent qubit decoherence [6,7,8], direct simulation of an environment [9,10,11], implementing Kraus maps / Lindblad operators [12,13,14,15,16], variational techniques [17,18], and more [19,20]. Since Barreiro et al first demonstrated their open-system quantum simulator [21], current early-stage dissipative simulations of quantum systems in the areas of quantum chemistry and physics [19,12,7,22] have been completed.…”
Section: Introductionmentioning
confidence: 99%
“…Here ε s ≡ −2 cos(k + Ωs∆t) is the dispersion relation, n F [x] is the Fermi-Dirac distribution, and the angles at step s are defined byθ s = 2 sin −1 2Γ∆t e βεs + 1and φ s = 2 sin −1 2Γ∆t e −βεs + 1 (S 19). …”
mentioning
confidence: 99%
“…An intriguing question to be explored is the role of interaction entering the unitary Hamiltonian for the entanglement transitions in various many-body problems. An experimental implementation of the open quantum Ising chain on IBM's quantum hardware was realized very recently [70]. 1, but for M = 0.5, P = 1 and ∆ = 0, such that the system is non-interacting.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It had the advantage compared to a variational quantum eigensolver (VQE) of not using ancilla qubits. The method was applied to the quantum computation of chemical energy levels on NISQ hardware [32][33][34][35], and the simulation of open quantum systems [36]. The impact of noise on QITE in NISQ hardware was addressed in [37] using error mitigation and randomized compiling.…”
Section: Introductionmentioning
confidence: 99%